Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1097/ta.0000000000003258
|View full text |Cite
|
Sign up to set email alerts
|

Use of regional analgesia and risk of delirium in older adults with multiple rib fractures: An Eastern Association for the Surgery of Trauma multicenter study

Abstract: BACKGROUND:Single-center data demonstrates that regional analgesia (RA) techniques are associated with reduced risk of delirium in older patients with multiple rib fractures. We hypothesized that a similar effect between RA and delirium would be identified in a larger cohort of patients from multiple level I trauma centers. METHODS:Retrospective data from seven level I trauma centers were collected for intensive care unit (ICU) patients 65 years or older with ≥3 rib fractures from January 2012 to December 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In a study by O’Connell et al , reduced delirium rates were observed in elderly patients with rib fracture after incorporation of regional analgesia techniques. 21 This was thought to be due to a decrease in morphine equivalents in the regional analgesia group. 21 22 Although our study demonstrated an upward trend in regional techniques, this did not translate into a significant decrease in oral morphine equivalents administered to patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by O’Connell et al , reduced delirium rates were observed in elderly patients with rib fracture after incorporation of regional analgesia techniques. 21 This was thought to be due to a decrease in morphine equivalents in the regional analgesia group. 21 22 Although our study demonstrated an upward trend in regional techniques, this did not translate into a significant decrease in oral morphine equivalents administered to patients.…”
Section: Discussionmentioning
confidence: 99%
“… 21 This was thought to be due to a decrease in morphine equivalents in the regional analgesia group. 21 22 Although our study demonstrated an upward trend in regional techniques, this did not translate into a significant decrease in oral morphine equivalents administered to patients. The limited sample size of our study is a key factor in this lack of statistical significance, with only 48 out of 487 patients receiving regional techniques.…”
Section: Discussionmentioning
confidence: 99%
“…These continuous catheter infusion techniques are increasingly focussed on myofascial plane blocks such as serratus anterior blocks and erector spinae blocks [ 19 ]. Benefits in the elderly, particularly in opioid sparing and reduction of delirium, have been demonstrated [ 20 ]. Interestingly, that study found no impact on mortality, or respiratory complications in a cohort of patients greater than 65 years.…”
Section: Discussionmentioning
confidence: 99%
“…A recent EAST multicenter trial by O’Connell et al in 2021 demonstrated that in older adults with significant thoracic trauma, regional anesthesia as a part of multimodal pain management reduced the risk of delirium in this population by 35%. The benefits of regional anesthesia for delirium prevention in this group are thought to arise from a combination of secondary benefits, such as earlier mobilization, better sleep, and fewer deliriogenic medications [15 ▪▪ ].…”
Section: Elderly Patients With Rib Fracturesmentioning
confidence: 99%